Angle-resolved low-coherence interferometry: an optical biopsy technique for clinical detection of dysplasia in Barrett''s esophagus. (January 2012) - Zhu, Yizheng; Terry, Neil G; Wax, Adam
Angle-resolved low-coherence interferometry (a/LCI) is an optical biopsy technique that measures scattered light from tissue to determine nuclear size with submicron-level accuracy. The a/LCI probe can be deployed through the accessory channel of a standard endoscope and provides feedback to physicians to guide physical biopsies. The technique has been validated in animal and ex vivo human studies, and has been used to detect dysplasia in Barrett''s esophagus patients in vivo . In a recent clinical study of 46 Barrett''s esophagus patients, a/LCI was able to detect dysplasia with 100% sensitivity and 84% specificity. This report reviews the technique and discusses its potential clinical utility.